Prevalence and Factors Associated with Reproductive Tract Infections in Gongolia Village, Rupandehi District, Nepal - Pravina Kafle; Shiva Shankar Bhattarai (Hindawi Limited, 2016)
Objective. To determine the prevalence of reproductive tract infection (RTI) and its associated factors among married women of reproductive age group (15-49 yrs). Method. A cross sectional approach was employed. The study collected data of symptoms suggestive of RTI experienced in the previous six months according to World Health Organization (WHO) syndromic approach guideline. A structured interviewer administered questionnaire was used to collect data and data were entered into EPI data and transferred into SPSS (16 version) for further analysis. Chi square was used for statistical analysis. Result. Among 258 married women the prevalence of symptoms suggestive of RTI was found to be 39.9%. Low back pain, vaginal discharge, and low abdominal pains were common symptoms reported in study. Irregular menstrual cycle, sexual contact during menstruation, marriage below 19 yrs, pregnancy below 20 yrs, high parity, delivery at home, and use of temporary family planning device were significant risk factors for prevalence of RTI symptoms. Conclusion. RTI still remains neglected by married women. Training and education session needs to be carried out to identify the early symptoms of RTI. Awareness about marriage and pregnancy after 19 yrs of age, sex education, delivery at health institution by health personnel, menstrual and personnel hygiene, and use of the condom are needed for prevention of RTI.